Erasmus syndrome: Association of silicosis and systemic sclerosis - Reena K Sharma; Anjna K Sharma; Anuj Sharma (Wolters Kluwer Medknow Publications, 2018)
Silicosis is an inflammatory disease of the lung characterized by irreversible lung fibrosis which develops from prolonged pulmonary inhalation and retention of crystalline silica and immune reaction. It mainly appears as an occupational hazard in persons involved in stone-quarrying, mining, and sand blasting. Crystalline silica is not only known to be responsible for silicosis but also for other autoimmune diseases including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA)-Caplan syndrome, systemic sclerosis (SSc), and antineutrophil cytoplasmic antibody (ANCA)-related vasculitis. Erasmus syndrome is the association of silica exposure and subsequent development of SSc. The limited numbers of cases reported in the literature were miners and only sporadically involved in other professionals. Here, we report a case of a 52 -year-old stone cutter who developed silicosis and SSc after 25 years of exposure.